Pœ̄t lōk suntharī nai withī manutsayasāt - Chātchāi Muksong,Nanthanut ʻUdomlamun,Surachēt Suklāpkit,Thanō̜m Chāphakdī (Sayām Parithat, 2020)
Conference papers on aesthetic dimensions in humanities.
Includes bibliographical references
Keywords: Aesthetics; Humanities